Assessment of retinal vascular calibres as a biomarker of disease activity in birdshot chorioretinopathy. Issue 2 (6th August 2016) - Agrawal, Rupesh; Joachim, Nichole; Li, Ling‐Jun; Lee, Jiaying; Agarwal, Aniruddha; Sim, Dawn A.; Keane, Pearse A.; Liew, Gerald; Pavesio, Carlos E.
Abstract: Purpose: Birdshot chorioretinopathy (BCR) is a potentially blinding ocular disorder involving the retinal vasculature and choroid without any systemic manifestations. The objective of the study was to describe vascular calibre changes in BCR and analyse the possibility of this optical biomarker for staging and monitoring disease activity in BCR. Methods: This retrospective case–control study at a tertiary referral eye centre in the UK included 33 eyes from 21 patients with BCR and equal number of eyes from control subjects. Diagnosis of BCR was confirmed on fundus fluorescein and indocyanine green angiography. Vascular calibres were measured using validated semiautomated software. Results: Patients with BCR had smaller retinal venular calibres central retinal venular equivalent (CRVE) than controls (211.3 versus 227.9 μ m, p = 0.008). After adjusting for variables, the difference between the two groups for CRVE at baseline was statistically significant based on two different analysis methods. Central retinal venular equivalent (CRVE) was lower at the 6‐month follow‐up visit (206.2 versus 213.8 μ m, p‐value = 0.03), and arteriole‐to‐venule ratio was larger (0.74 versus 0.71, p = 0.04) in subjects with BCR. Arteriolar calibre (CRAE) remained the same. Conclusion: This study provides novel insight into the pattern of vascular involvement in BCR. There was significant difference in the CRVE in patients with BCR. More studies are needed to correlate this data with visual function and treatment outcome and to validate the findings.